2018
DOI: 10.1111/andr.12522
|View full text |Cite
|
Sign up to set email alerts
|

Penile lengthening with porcine small intestinal submucosa grafting in Peyronie's disease treatment: long‐term surgical outcomes, patients’ satisfaction and dissatisfaction predictors

Abstract: PLP using a Surgisis ES is a valuable surgical option for the treatment of PD with severe PC. Although it results in high rates of long-term patient-reported overall satisfaction, possible outcomes such as postoperative ED must be acknowledged. TDA is a strong predictor for postoperative ED and should be considered in clinical practice to classify patients in low- or high-risk for postoperative ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 29 publications
(50 reference statements)
1
29
3
Order By: Relevance
“…Kovac et al and Chung et al included 36 and 46 patients, respectively, who were recruited over a time period of six years and also received dermal and synthetic grafts [12] or dermal and cadaveric pericardial grafts [13], which may render comparison of results difficult. Morgado et al focused on patient satisfaction with sex life after surgery [16]. Other studies reported less subjective penile shortening in 5–71% of patients [12,13,14,15,16], compared to almost 97% of patients in the present study.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Kovac et al and Chung et al included 36 and 46 patients, respectively, who were recruited over a time period of six years and also received dermal and synthetic grafts [12] or dermal and cadaveric pericardial grafts [13], which may render comparison of results difficult. Morgado et al focused on patient satisfaction with sex life after surgery [16]. Other studies reported less subjective penile shortening in 5–71% of patients [12,13,14,15,16], compared to almost 97% of patients in the present study.…”
Section: Discussioncontrasting
confidence: 42%
“…Previously, others have reported inconsistent findings on patient satisfaction with surgical outcome following SIS grafting. Some studies found high satisfaction rates of 82–89% [13,14,15,16], while Chung et al reported that more than 65% of patients were not satisfied with surgical outcome [12]. Variable findings among studies regarding patient satisfaction with surgical outcome may be due to differences in patient characteristics, follow-up, study design, and methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Penile Tissue Collection and Processing. Samples of CC of penis were obtained from organ donors during organ harvesting for transplant program or, alternatively, from patients submitted to programmed surgeries for correction of penile deviation or implantation of penile prosthesis [37] after informed consent. Patient's age was comprised between 43 and 63 years.…”
Section: Methodsmentioning
confidence: 99%
“…The tunical defect area (TDA) positively correlated to the development of postoperative ED with the highest predictability in defects ≥ 21.9 cm 2 , supporting TDA as a potential predictor of postoperative ED development. In conclusion, the investigators regarded SIS grafting as a successful approach in terms of patient satisfaction, provided all risks and potential complications were adequately disclosed preoperatively 47 …”
Section: Postoperative Considerations: (Surgical Outcomes/patient Rehmentioning
confidence: 99%